Analysis of Factors that Influence the Participation of Women of Childbearing Age in the Examination of Visual Acetic Acid Inspection (IVA) in Kanor Public Health Center, Bojonegoro Regency - Agung Cahyono; Nurwijayanti Nurwijayanti; Ratna Wardani (Journal for Quality in Public Health, 2021)
Cervical cancer is the most common case and almost 70% of it is found in an advanced stage condition (> stage IIB). This is because the screening implementation is still low, which is <5%. In fact, the ideal screening implementation is 80%. Actually, early-stage cervical cancer can be diagnosed by performing a cytological examination through IVA. Nearly 50% of people with cervical cancer do not do IVA. The purpose of this study was to determine the effect of health services, maternal motivation, level of knowledge, and husband's support for the participation of women of childbearing age in the IVA examination at the Kanor Health Center. This research method is analytic research with cross sectional approach. The study population was all women of childbearing age between 30 and 50 years in the Kanor Health Center area. Proportional random sampling technique with a total sample of 300 people. Data analysis techniques using multiple logistic regression. The results showed that the variables that influenced participation in the IVA examination were health services (p = 0,000 and beta = 0.050) and maternal motivation (p = 0,000 and beta 0.037). While the variables that did not affect the participation of IVA examination were knowledge and husband support. The results of data analysis showed that the most dominant variable affecting the participation of women of childbearing age in the IVA examination was health services with a p value of 0.000 and an Odd Ratio of 0.050, which means that good health services will have a greater influence on the participation of women of childbearing age in IVA examinations by 0.050 times compared to poor health services. Therefore, it is necessary to have health promoter staff to provide information about health services as well as education or health education about early detection of cervical cancer through examinations.